PENGARUH PELATIHAN KERJA, KOMPENSASI FINANSIAL DAN PENGEMBANGAN KARIR TERHADAP KINERJA SATPAM PT. ASTA KRIDA RUMENTANG - Joni Hermanto (Universitas Sains dan Teknologi Komputer, 2023)
The subjects of this quantitative research were employees of PT. Asta Krida RumentangSurakarta. Comprehensive sampling technique from the existing population, namely 54 employees. The research results obtained the multiple linear regression equation Y = -2.242 + 0.902X1 + 0.177X2 + 0.009X3. T test relating to Job Training on PT Performance. For Asta Krida Rumentang, the calculated t value = 30.645 > t table = 2.00 and the significance value is 0.000, so thereis an influence. T test relating to Financial Compensation on PT Performance. Asta Krida Rumentang obtained the results of t = 3.498 > t table = 2.00, so there is an influence. T test relating to career development on PT performance. Asta Krida Rumentang obtained the results of t = 0.251 < t table = 2.00, so there is no influence between career. development on PT performance. AstaKrida Rumentang. The joint test or F test resulted in calculated F = 339.389 > F table = 2.79, and the significance level was 0.000 < 0.05, so there was a joint influence. Obtained for R2 is 0.953 or 95.3%, meaning that together there is an influence between the independent variables, namely Job Training, Financial Compensation and career development on PT Performance. Asta Krida Rumentang was 95.3%, while the 4.7% was influenced by other factors, which were not researched, such as price, brand image and so on.